Post a New Question


posted by .

how do you solve this by substitution:
step by step

1. 5x-y=16

2. 3x-3y=9

3. x=-6y

thank you!

  • algebra! -

    3. x = -6y

    y = 2/3x + 5

    y = 2/3(-6y) +5

    y = -4y + 5

    5y = 5

    y = 1

    Substitute -6y for x in second equation and solve for y. Insert that value into the first equation and solve for x. Check by inserting both values into the second equation.

    Use the same process for the first two equations.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question